Effective psychological treatment in psychotraumatology - Kazlauskas, E. (Psichologija, 2013)
The present article gives an overview of the psychological treatments of psychological trauma. The article is oriented towards practitioners who want to update their knowledge of the recent developments in psychotraumatology. The research findings, based on meta-analyses and good practice guidelines, are presented and the issues related to the implementation of evidence-based treatments are discussed.The study has shown that the critical stress incident debriefing developed by J. T. Mitchell in 1983 (or psychological debriefing) is not recommended immediately after trauma. Metaanalysis (Rose et al., 2003; van Emmeric et al., 2002) revealed no positive long-term effects of debriefing immediately after trauma, with indications of negative outcomes in some studies. Practical guidelines of the International Society of Traumatic Stress Studies, as well as other guidelines, do not recommend debriefing as a regular procedure for all survivors. Practical, social, or legal assistance provided in an empathic way is recommended during the first month after the trauma.  Meta-analytical studies published since 1998 concerning the effectiveness of posttraumatic stress disorder treatments demonstrated the efficacy of trauma-focused cognitive-behavioral therapies (TF-CBT) and eye movement reprocessing and desensitization therapy (EMDR). Evidence from studies on the effects of brief eclectic psychotherapy for posttraumatic stress disorder (BEPP), developed by B. Gersons, internet-based treatments, and virtual reality are promising, and these treatments in the future are possible effective alternatives for TF-CBT and EMDR in evidence-based practice. Psychological treatments should be the first option for the treatment of PTSD, with medication used only when the appropriate psychological treatments are unavailable or the client prefers medication over psychosocial treatment.While a number of RCT studies have shown the efficacy of TF-CBT and EMDR treatment for PTSD, there is still a gap between research and everyday clinical practice. From the practitioner’s point of view, the transfer of manual-based methods from RCT efficacy studies to daily practice is not easy. Clinicians are facing complicated cases, and comorbid disorders are widely prevalent with PTSD. We must also be aware that with the new treatments developed, training of these methods and particularly the availability of systematic supervisions are not always easily accessible; this slows down the dissemination and implementation of evidence-based treatments. Clinicians have to take their own responsibility for selecting what is best for a particular client; however, practitioners also need to make decisions based on what science shows to be the most effective treatment.
Keywords: psychological trauma; posttraumatic stress disorder; effectiveness of treatment